Prevalence of shigellosis diarrhoea in a paediatrics population: hospital based survey in Bangui, Central African Republic - Alexandre Manirakiza; Prisca Megne-Boudjeka; Gustave Bobossi-Serengbe; Raymond Bercion; Alain Le Faou (Journal of Infection in Developing Countries)
Introduction: Shigellosis is still a major public health problem in sub-Saharan countries, especially among children.